Intravascular lithotripsy in chronic total occlusion percutaneous coronary intervention: Insights from the PROGRESS‐CTO registry. Issue 4 (2nd August 2022) - Kostantinis, Spyridon; Simsek, Bahadir; Karacsonyi, Judit; Davies, Rhian E.; Benton, Stewart; Nicholson, William; Rinfret, Stephane; Jaber, Wissam A.; Raj, Leah; Sandesara, Pratik B.; Alaswad, Khaldoon; Basir, Mir Babar; et al.
Abstract: Background: The use of intravascular lithotripsy (IVL) in chronic total occlusion (CTO) percutaneous coronary intervention (PCI) has received limited study. Methods: We analyzed the baseline clinical and angiographic characteristics and procedural outcomes of 82 CTO PCIs that required IVL at 14 centers between 2020 and 2022. Results: During the study period, IVL was used in 82 of 3301 (2.5%) CTO PCI procedures (0.4% in 2020 and 7% in 2022; p for trend < 0.001). Mean patient age was 69 ± 11 years and 79% were men. The prevalence of hypertension (95%), diabetes mellitus (62%), and prior PCI (61%) was high. The most common target vessel was the right coronary artery (54%), followed by the left circumflex (23%). The mean J‐CTO and PROGRESS‐CTO scores were 2.8 ± 1.1 and 1.3 ± 1.0, respectively. Antegrade wiring was the final successful crossing strategy in 65% and the retrograde approach was used in 22%. IVL was used in 10% of all heavily calcified lesions and 11% of all balloon undilatable lesions. The 3.5 mm lithotripsy balloon was the most commonly used balloon (28%). The mean number of pulses per lithotripsy run was 33 ± 32 and the median duration of lithotripsy was 80 (interquartile range: 40−103) seconds. Technical and procedural success was achieved in 77 (94%) and 74 (90%) cases, respectively. Two (2.4%) Ellis Class 2 perforations occurred after IVL use and were managed conservatively. Conclusion: IVL is increasingly being used in CTO PCI with encouraging outcomes.